Building information modeling (BIM) capabilities in quantity surveying practice during pre-construction stage : the relationship with project performance / Wong Phui Fung - Wong, Phui Fung (2015)
Poor cost performance in the construction industry has been widely reported in numerous studies. Cost overrun and inaccurate estimate are the pitfalls that affect the project performance. It has been noted that quantity surveyors (QSs) play a major role in providing and managing project cost in the construction industry. Several authors have addressed that the traditional manual methods adopted by QSs are inefficient and the accuracy of the project cost is affected. Recent evidences suggest that implementation of building information modeling (BIM) is a potential solution that can rectify the inefficiencies and improve cost accuracy. However, the adoption of BIM among QSs is slow due to lack of awareness and limited study on the BIM capabilities in quantity surveying practice. There have been little discussions pertaining to the relationship between BIM capabilities in quantity surveying practice during pre-construction stage and project performance. Hence, this research developed a framework on the relationships between BIM capabilities in quantity surveying practice during pre-construction stage and project performance for time, cost, and quality aspects. Through the study of this relationship, the effects of the BIM capabilities in quantity surveying upon the project performance had been further investigated. In this research, a mixed method of quantitative and qualitative was adopted. A sequential four-phased research approach was designed for data collection and interpretation. This research began with a detailed literature review and 11 BIM capabilities were discovered in quantity surveying practice. Next, preliminary interviews were conducted with 8 QSs to confirm the identified capabilities. Following this, questionnaires were distributed to 131 quantity surveying organizations after sampling determination. Several analyses were performed to examine the relationship between BIM capabilities and project performance. BIM capabilities were ranked using relative importance index. Correlation analysis was performed to explore the related BIM capabilities to the project performance. Then, logistic regression was conducted to further examine the relationship between BIM capabilities and project performance. At the last phase of the research, qualitative semi-structured interviews were executed to validate the questionnaires survey results. 15 QSs were interviewed to obtain further details on the identified relationship by ascertaining their experiences and views. The findings revealed that BIM capabilities in quantity surveying practice during pre-construction stage were significantly correlated and regressed to the project performance. For time aspect, capabilities of cost checking and visualization affected the performance. For cost aspect, capabilities of generate cost estimate for various design alternatives and automatically quantification for bill of quantities preparation affected the performance. For quality aspect, capabilities of clash detection and visualization affected the performance. These relationships were developed in a framework to depict how BIM capabilities were related to the project performance to facilitate understanding and awareness among QSs. The research findings provided an insight to QSs on how to achieve better project performance by adopting BIM in their practice at an early stage. Thus, QSs should consider the identified BIM capabilities and refer to the relationships portrayed in the framework in their practice at the early stage for better project outcomes.